2018
DOI: 10.4067/s0717-95022018000200687
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphological Study of Placenta in Gestational Diabetes Mellitus

Abstract: SUMMARY:Evidence from the literature shows that well-controlled glucose levels during pregnancy are usually associated with normal placental morphology. The aim of this study was to identify the placental changes attributed to maternal hyperglycemia. A total of 20 placentae were selected for study from a tertiary care medical center in Makkah city, Saudi Arabia. Out of 20, 10 placentae were from patients diagnosed with GDM based on IADSPG criteria, and 10 placentae were from patients with normal pregnancies wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 9 publications
1
7
0
1
Order By: Relevance
“…2B). This results matched with other studies that observed a histological change in GDM placentae represented by stromal fibrosis 6 Syncytial knots were formed in more than onethird of the examined villi, in 28 placentae (70 %) from the GDM group. However, this deviation from the normoglycemic group was noticed only in 4 placentae (20 %) (Fig.…”
Section: Figure (1): Light Microscopical Appearance Of Normoglycemic Pregnant Women Placenta Showing Microvilli (V) With Narrow Intervillsupporting
confidence: 91%
See 3 more Smart Citations
“…2B). This results matched with other studies that observed a histological change in GDM placentae represented by stromal fibrosis 6 Syncytial knots were formed in more than onethird of the examined villi, in 28 placentae (70 %) from the GDM group. However, this deviation from the normoglycemic group was noticed only in 4 placentae (20 %) (Fig.…”
Section: Figure (1): Light Microscopical Appearance Of Normoglycemic Pregnant Women Placenta Showing Microvilli (V) With Narrow Intervillsupporting
confidence: 91%
“…This change was observed in the normoglycemic group in only 2 placentae (10 %), in the GDM group in 26 placentae (65 %). El Sawy et al 6 and other study 15 confirm that one of indicator of placentae tissue of GDMpregnant is cytotrophoblast cells proliferation 6 .…”
Section: Figure (1): Light Microscopical Appearance Of Normoglycemic Pregnant Women Placenta Showing Microvilli (V) With Narrow Intervillmentioning
confidence: 85%
See 2 more Smart Citations
“…Moreover, unbalanced O-GlcNAcylation levels favor endothelial dysfunction in uterine arteries, which is important for uteroplacental circulation and this is partly modulated by OGT (32). These results might partly explain the structural and functional immaturity of placentas exposed to hyperglycemia and its effect on maternal-fetal interactions (33).…”
Section: Placenta Growth and Developmentmentioning
confidence: 99%